Comparative chloroplast genomics of Rutaceae: structural divergence, adaptive evolution, and phylogenomic implications - Chen, Yichao; Liu, Ningge; Wang, Hong; Luo, Huifeng; Xie, Zhiliang; Yu, Hongao; Chang, Yaojun; Zheng, Bosheng; Zheng, Xinchen; Sheng, Jun; Jiang, Yajie; Ye, Shuzhe; et al. (Frontiers in Plant Science, 2025)
The study of chloroplast genome evolutionary dynamics provides critical insights into plant adaptive evolution and phylogenetic relationships. This research conducted a systematic comparative analysis of chloroplast genomes across 35 species within the Rutaceae family. All genomes displayed the typical quadripartite structure, with sizes ranging from 155 to 161 kb, GC contents between 38.17% and 38.83%, and gene counts varying from 122 to 144. Structural conservation was high across species, with variations mainly localized at the boundaries of inverted repeat (IR) regions. AT-rich mononucleotide simple sequence repeats (SSRs) were dominant and primarily distributed in non-coding regions. Collinearity analysis revealed high sequence conservation alongside lineage-specific rearrangements. Relative synonymous codon usage (RSCU) analysis revealed significant heterogeneity among species, with values ranging from 0.386 to 1.797. ENC-GC3s, GC3-GC12, and PR2 analyses indicated a marked deviation from neutral evolution. Selection pressure analysis indicated strong purifying selection (Ka/Ks < 0.2) acting on photosynthetic system genes, while certain genes (e.g., matK, rpl20) exhibited signals of positive selection, highlighting adaptive evolutionary features in specific genomic regions. Phylogenetic reconstruction placed Murraya paniculata within a clade containing other Murraya species, closely related to Citrus and Clausena, reflecting morphological and biogeographic patterns. This study provides a molecular framework for taxonomic revision in Rutaceae and enhances understanding of chloroplast genome evolution in the family.